Perceived Impact of Microfinance on Livelihood Improvement in Kaski District of Nepal - Dhungana, Bharat Ram (Journal of Innovation in Academia, 2023)
This paper examines the perceived impact of microfinance on livelihood improvement in Kaski district of Nepal. The study is based on a primary survey limited to five MFIs working in rural parts of Kaski district. The impact of microfinance services on people's livelihoods was examined using a descriptive and explanatory research including paired sample t-test, and Wilcoxon signed-rank test The livelihood status of the clients has been measured in terms of economic (microbusiness creation, income level, saving habits, productive investment, consumption, and capital expenditures) and social condition (educational status, health status, women empowerment, and social networking) of the clients after microfinance intervention. The researcher randomly selected 150 clients involved in microfinance institutions for the last three or more years. Microfinance significantly affects the livelihood and raises standards of living. The study finds a significant impact of microfinance on the livelihood improvement of poor and marginalized people. Microfinance interventions have significantly improved clients' economic condition, including microbusiness creation, income level, saving habits, productive investment, consumption, and capital expenditures. The social conditions, particularly educational status, health status, women empowerment, and social networking of clients, have significantly improved. Microfinance can be useful for fostering economic growth and enhancing the lives of low-income people and communities, even though its efficacy is disputed. The regulatory authority should develop sound financial and social outreach efficiencies of microfinance institutions to ensure both the welfare of clients and the sustainability of micro institutions.